MTOR (Mechanistic Target of Rapamycin) Inhibition Decreases Mechanosignaling, Collagen Accumulation, and Stiffening of the Thoracic Aorta in Elastin-Deficient Mice. Issue 9 (September 2017) - Jiao, Yang; Li, Guangxin; Li, Qingle; Ali, Rahmat; Qin, Lingfeng; Li, Wei; Qyang, Yibing; Greif, Daniel M.; Geirsson, Arnar; Humphrey, Jay D.; Tellides, George
Abstract : Objective—: Elastin deficiency because of heterozygous loss of an ELN allele in Williams syndrome causes obstructive aortopathy characterized by medial thickening and fibrosis and consequent aortic stiffening. Previous work in Eln -null mice with a severe arterial phenotype showed that inhibition of mTOR (mechanistic target of rapamycin), a key regulator of cell growth, lessened the aortic obstruction but did not prevent early postnatal death. We investigated the effects of mTOR inhibition in Eln -null mice partially rescued by human ELN that manifest a less severe arterial phenotype and survive long term. Approach and Results—: Thoracic aortas of neonatal and juvenile mice with graded elastin deficiency exhibited increased signaling through both mTOR complex 1 and 2. Despite lower predicted wall stress, there was increased phosphorylation of focal adhesion kinase, suggestive of greater integrin activation, and increased transforming growth factor-β–signaling mediators, associated with increased collagen expression. Pharmacological blockade of mTOR by rapalogs did not improve luminal stenosis but reduced mechanosignaling (in delayed fashion after mTOR complex 1 inhibition), medial collagen accumulation, and stiffening of the aorta. Rapalog administration also retarded somatic growth, however, and precipitated neonatal deaths. Complementary, less-toxic strategies to inhibit mTOR via altered growth factor and nutrient responses were not effective. Conclusions—: In addition to previously demonstrated therapeutic benefits of rapalogs decreasing smooth muscle cell proliferation in the absence of elastin, we find that rapalogs also prevent aortic fibrosis and stiffening attributable to partial elastin deficiency. Our findings suggest that mTOR-sensitive perturbation of smooth muscle cell mechanosensing contributes to elastin aortopathy. Abstract : Supplemental Digital Content is available in the text.